القصور الكلوي المزمن و تأثيره على مستوى التوافق الزواجي لدى الزوجة المصابة - معمري, حفيظة (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
تهدف الدراسة الحالية إلى توضيح كيف يؤثر القصور الكلوي المزمن. على مستوى التوافق الزواجي لدى الزوجة، ومعرفة مستوى توافقها وأهم العوامل التي تؤثر على التوافق الزواجي بسبب المرض المزمن حيث اعتمدنا في الدراسة على حالتين من النساء المتزوجات مصابات بالقصور الكلوي المزمن، مستخدمين في ذلك المنهج العيادي وكل من المقابلة النصف موجهة وملاحظة ودراسة الحالة مع تطبيق مقياس التوافق الزواجي لزاهية مسعودي. وتم عرض الحالات ومناقشتها من خلال المعطيات المتحصل عليها من دليل المقابلة المكون من مجموعة من الأسئلة قسمت إلى محاور وقد توصلنا في الأخير إلى أن مستوى التوافق الزواجي منخفض وأن هناك عدة عوامل مؤثرة على التوافق الزواجي من بينها العامل النفسي والاجتماعي والاقتصادي.
دراسة عيادية في المركز الاستشفائي الجامعي مستغانم
The aim of the study is to clarify how chronic. Renal insufficiency affects marital compatibly, for the wife and to determine her level of compatibility and the most important factors, which affect marital compatibility through chronic illness. In our study, we relied on two cases of married Women with chronic renal insufficiency, using a clinical approach and semi-structured interviews. We observed and studied a Case while applying the marital compatibility scale by Ramia Masoudi. The cases were Presented and discussed based on the data obtained from the interview guide, consisting of a set of questions divided into axes in the end, We Concluded that the level and of marital compatibility is low and that there are several factors controlling it, the most important of which are psychological, economic, and social effects.
Keywords: القصور الكلوي المزمن، التوافق الزواجي: chronic Kidney disease, Marital compatibility.